2006
DOI: 10.1088/0967-3334/27/3/005
|View full text |Cite
|
Sign up to set email alerts
|

Gastric impedance spectroscopy in elective cardiovascular surgery patients

Abstract: Impedance spectroscopy has been proposed as a method of monitoring mucosal injury due to hypoperfusion and ischemia in critically ill patients. The present study characterizes human gastric impedance spectral changes under gastric hypoperfusion in patients undergoing cardiovascular surgery, and evaluates spectral differences between patients with no evidence of gastric ischemia and complications, and patients who developed ischemia and complications. Cole and Kun parameters were calculated over time to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
0
18
0
3
Order By: Relevance
“…We proposed that bioimpedance and particularly gastric reactance is an early indicator of ischemia and we developed some studies that confirm the prognostic and diagnostic value of these measurements [20, 21]. However, before we may advocate the clinical use of this technology we need to first answer the following questions: (1) Can we quantify oedema and tissue damage from impedance parameters?, (2) Can we use this information to improve patient management and treatment?…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that bioimpedance and particularly gastric reactance is an early indicator of ischemia and we developed some studies that confirm the prognostic and diagnostic value of these measurements [20, 21]. However, before we may advocate the clinical use of this technology we need to first answer the following questions: (1) Can we quantify oedema and tissue damage from impedance parameters?, (2) Can we use this information to improve patient management and treatment?…”
Section: Discussionmentioning
confidence: 99%
“…Gastric reactance shows high sensitivity to predict outcome, compared with some hemodynamic and regional perfusion variables. 25,26 Low-frequency gastric reactance, X L , had a significant predictive value of postoperative persistent shock requiring more than 48 h of vasopressors and associated complications, before, during, and after surgery (P < 0.05) (see Table 1). Patients with a high reactance (X L > 26) before surgery had a significantly higher incidence of complications, higher mortality, and more days in the intensive care unit (ICU) than patients with a low reactance (X L < 13).…”
Section: Model Based On Antonsson's Validation Study Ofmentioning
confidence: 98%
“…Our research group reported a relationship between bioimpedance changes with tissular damage level generated by ischemia by means of confocal endomicroscopy and light microscopy 21 ; also two animal models of shock were made, one to monitor ischemic injury of the intestinal mucosa in a hemorrhagic shock model in rabbits, 22 other to show that combined splanchnic tissue indicators have the potential of been used as complementary tools for guiding a treatment in septic shock. 23 Finally, we developed some human studies to evaluate the clinical significance of the impedance measurements: in healthy volunteers, 24 in elective cardiovascular surgery patients, [25][26][27] and the last one in general critically ill patients. 28 This document attempts to summarize our work to date, showing the importance of gastric ischemia monitoring and main animal and human results.…”
Section: Impedance Spectroscopy (Is) Of Biological Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the technique, an impedance spectroscopy probe and nasogastric tube ISP/NGT [5] allows the direct acquisition of an electric impedance spectrum of the mucosa, which can be used to identify and continuously monitor the level of tissue damage. N Our research group recently reported that hypoperfusion and ischemia cause changes in the impedance spectra of the gastric wall in cardiovascular surgery patients [6], proposing that this technology may be a useful prognostic and diagnostic monitoring tool.…”
Section: Introductionmentioning
confidence: 99%